Mehmet S. Aydın'ın Hayali: Aşırı Rasyonel Din Felsefesi Tavrının Eleştirisi - Tüzer, Abdüllatif (My University, 2016)
Undoubtedly today, Mehmet S. Aydın is the most prominent philosopher of religion in Turkey. It seems to me that Prof. Aydın shows quite extreme rational, analytical, universalist and liberal approach in philosophizing. In a sense, with a rational and liberal spirit, he criticizes the tradition and religious texts and thus tries to resolve the difficulties in tradition through modernizing the religion. It is undoubtedly true that he has been considerably successful in his attempt and established an academic circle - even a tradition - comprising plenty of followers. To establish an ethical social order with liberal and rational character in which anyone, believer or unbeliever, is able to live freely as he wishes is his dream. It is not only a subjective dream but also what Koran seeks to realize. The realization of this dream, according to Aydın, depends on the demonstration of that Islam is a purely reason-based, universal and liberal religion to the extent that it makes no room for irrationality. In this way, Aydın tends to show that Islam is an universal, rational and liberal religion only when it is emptied of its historicity
Mehmet S. Aydın's Dream: Critique of Extreme Rational Approach in Philosophy of Religion
Keywords: Felsefe